Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1167/iovs.12-10109
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Astrocytes in a Glaucomatous Optic Nerve

Abstract: Confirming results after optic nerve crush, astrocytes in glaucomatous optic nerves had thickened and simplified processes, and reduced spatial coverage. We also found evidence of localized sprouting of new processes in early stages of the disease, before detectable changes in ganglion cell number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 27 publications
(51 reference statements)
7
84
2
Order By: Relevance
“…Since we evaluated overall labeling intensity, increases in GFAP or glutamine synthetase levels can be attributed to either increased expression on a per cell basis, which accompanies hypertrophy, or an increase in density. Both hypertrophy and changes in cell density are hallmarks of glial reactivity and have been described in various retinal diseases, including glaucoma [5,[52][53][54][55][56][57][58]. In all groups, we noted instances of changes in expression/cell and, for astrocytes, differences in cell density.…”
Section: Discussionsupporting
confidence: 52%
“…Since we evaluated overall labeling intensity, increases in GFAP or glutamine synthetase levels can be attributed to either increased expression on a per cell basis, which accompanies hypertrophy, or an increase in density. Both hypertrophy and changes in cell density are hallmarks of glial reactivity and have been described in various retinal diseases, including glaucoma [5,[52][53][54][55][56][57][58]. In all groups, we noted instances of changes in expression/cell and, for astrocytes, differences in cell density.…”
Section: Discussionsupporting
confidence: 52%
“…Changes in astrocyte morphology, such as enlargement of the cell body and processes, as well as up-regulation of cytoskeletal and extracellular matrix proteins, have been observed in the retina and ONH in human glaucoma (Wang et al 2002;Inman and Horner 2007;Hernandez et al 2008;Kompass et al 2008;Nikolskaya et al 2009). Several studies have demonstrated that this reactivity and remodeling of astrocytes, and the increased deposition of extracellular matrix occur in early stages of experimental glaucoma (Johnson and Morrison 2009;Howell et al 2011a;Johnson et al 2011;Lye-Barthel et al 2013;Qu and Jakobs 2013). In fact, just a short term elevation of IOP induces rapid and reversible morphological…”
Section: Activation Of Astrocytes and Microglia In The Optic Nerve Hementioning
confidence: 99%
“…72 In a mouse model of glaucoma, astrocytes at the ONH become thicker in animals with moderate to severe disease and exhibited a simplified arbor network. 73 In human glaucoma patients, astrocytes express the cytokine TNFα and its receptor type 1 (TNF-R1) in the ONH. 58,74 Although the consequence of TNFα production is complicated and has been linked to neurodegeneration and neuroprotection, 58,75-81 astrocytes appear to be the primary producer of this cytokine in the ONH.…”
Section: Astrocytesmentioning
confidence: 99%